2012
DOI: 10.1063/1.4770268
|View full text |Cite
|
Sign up to set email alerts
|

Structural behavior of the acetylide carbides Li2C2 and CaC2 at high pressure

Abstract: The effects of high pressure (up to 30 GPa) on the structural properties of lithium and calcium carbide, Li(2)C(2) and CaC(2), were studied at room temperature by Raman spectroscopy in a diamond anvil cell. Both carbides consist of C(2) dumbbells which are coordinated by metal atoms. At standard pressure and temperature two forms of CaC(2) co-exist. Monoclinic CaC(2)-II is not stable at pressures above 2 GPa and tetragonal CaC(2)-I possibly undergoes a minor structural change between 10 and 12 GPa. Orthorhombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
7
28
0
Order By: Relevance
“…1940 cm -1 and 2060 cm -1 (Fig.3a). Nylén et al 23 reported that the C≡C stretching of Li 2 C 2 is at 1872 cm -1 in the Raman spectrum. We confirmed this with the Raman spectrum of our home-prepared Li 2 C 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1940 cm -1 and 2060 cm -1 (Fig.3a). Nylén et al 23 reported that the C≡C stretching of Li 2 C 2 is at 1872 cm -1 in the Raman spectrum. We confirmed this with the Raman spectrum of our home-prepared Li 2 C 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The multielement cases are needed to understand the feature of antimetallization from a different perspective at the fundamental level. For this purpose, the compounds of C m Li n are considered to be good examples for the understanding of the nature of physics (12)(13)(14). Examining their high-pressure behavior and exploring the possible metallization and superconductivity in this system are the focus of this work.…”
mentioning
confidence: 99%
“…The dumbbell units in Li 2 C 2 are expected to polymerize into zigzag chains of carbon atoms at pressures around 5 GPa, 6 and the system develops into semimetals (P -3m1-Li 2 C 2 ) and metals (Cmcm-Li 2 C 2 ) with polymeric anions (chains, layers, strands) by increasing pressure up to 20 GPa, and semimetallic P -3m1-Li 2 C 2 displays an electronic structure close to that of graphene. 4,7 By¯rst-principles total energy calculations, it is shown that in the athermal limit the orthorhombic polymorph of Cs 2 C 2 is more stable by about 7 kJ/mol with respect to the hexagonal modi¯cation, while for Rb 2 C 2 the orthorhombic polymorph is more stable by around 4 kJ/mol. 8 Prior to those theoretical researches, many experiments have been done to address their crystal structure.…”
Section: Introductionmentioning
confidence: 96%